Airway Management in a Patient with Extensive Maxillofacial Trauma: A Case Report - S. Deepak Shanker; Abhishek Nagarajappa; Reshma Kalagara; Christopher Dass (Journal of Trauma Anaesthesia, Resuscitation and Critical Care, 2026)
Managing the airway in patients with severe maxillofacial trauma remains one of the most demanding challenges in trauma care. Facial fractures not only distort normal anatomy but can also lead to airway obstruction, bleeding, aspiration risk, and difficulty in ventilation and intubation. Effective airway management in these cases depends on rapid decision-making, readiness for alternative airway techniques, and close coordination between the anesthesiologist and surgeon. A well-planned, individualized approach is essential to improve outcomes and minimize complications. We report the successful management of a patient with maxillofacial trauma in whom conventional difficult airway management techniques proved challenging.